ChemInform Abstract: Oxy‐Allyl Cation Catalysis: An Enantioselective Electrophilic Activation Mode. Issue 33 (27th July 2016) - Liu, Chun; Oblak, E. Zachary; Vander Wal, Mark N.; Dilger, Andrew K.; Almstead, Danielle K.; MacMillan, David W. C.
Abstract: Using a new amino alcohol catalyst, the enantioselective conversion of racemic α‐tosyloxy ketones into optically enriched α‐indolic carbonyls in the presence of electron‐rich indole nucleophiles is investigated.